Clinical electrophysiological effects of propranolol on normal sinus node function. Issue 6 (June 1979) - Vasquez, M; Chuquimia, R; Shantha, N; Khan, M; Narula, O S
Abstract : In 35 patients aged 18 to 69 years (mean 48) with clinical, electrocardiographic, or electrophysiological evidence of normal sinus node function, the effect of intravenous propranolol (0.1 mg/kg) was assessed on 3 indices of sinus node function. The drug significantly prolonged sinus node cycle length (12%), slightly prolonged the corrected sinus node recovery time (15%), and slightly but insignificantly lengthened sinuatrial conduction time. Propranolol may be administered safely in patients with normal sinus node function without the fear of producing severe sinus bradycardia, sinuatrial block, sinuatrial pauses, or prolonged sinus asystole, after spontaneous or stimulation-induced conversion of a tachycardia.